The Unicorn Is a Myth No More: A Ratio Decidendi Analysis on First Official Predatory Pricing Case in Indonesia - Zaid Zaid (Jurnal Penegakan Hukum dan Keadilan, 2022)
Predatory pricing has long been termed like a dragon or a unicorn because the practice is often considered irrational and therefore impossible to find or at least unlikely to work. However, the case that befell PT Conch South Kalimantan Cement broke the stigma in Indonesia, which was legally proven to practice predatory pricing through the Business Competition Commission Council (KPPU) Case Decision Number: 03/KPPU-L/2020. Considering that predatory pricing is complicated to prove because it requires certain elements to be fulfilled, this research then aims to analyze the predatory pricing elements, which became strong reasons that underlay the KPPU Council's determination of PT Conch South Kalimantan Cement as a predatory business actor so that it is entitled to be punished with billions of rupiah. By applying the normative method with a statutory, conceptual, and case approach through primary and secondary legal materials, which were analyzed by qualitative and prescriptive analysis, this study ultimately found the results that the elements in the form of business actors, supply, goods, selling at a loss or fixing a very low price, eliminating or shutting down the business of its competitors, the relevant market, and causing monopolistic practices and/or unfair business competition have become the ratio decidendi of the KPPU Council in determining the practice of predatory pricing. These reasons can then be used as decisions on similar issues in the future.